Masculinity, Media, and the American Presidency - Conroy, Meredith. author. aut Link
XIII, 195 p.
Keywords: This book analyzes the way media describe presidential candidates' character and the degree to which this discourse maintains a preference for masculinity in our politics, using content analysis of major print new media outlets.